2018
DOI: 10.1103/physrevmaterials.2.074006
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of exfoliated and epitaxial hexagonal boron nitride

Abstract: Hexagonal boron nitride (hBN) is an essential component in van der Waals heterostructures as it provides high quality and weakly interacting interfaces that preserve the electronic properties of adjacent materials. While exfoliated flakes of hBN have been extensively studied using electron transport and optical probes, detailed experimental measurements of the energy-and momentumdependent electronic excitation spectrum are lacking. Here, we directly determine the full valence band (VB) electronic structure of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…It consists in an exfoliated monoisotopic h 11 BN crystal transferred onto a graphene/SiC(0001) substrate. It should be pointed out that charging effects in photoemission from a bulk-like flake of an insulating material can be avoided by thinning the material in the exfoliation process and by placing it on a conductive support (38). Indeed, our recent photoemission study showed that it is possible to resolve the π-band of exfoliated hBN on epitaxial graphene (39).…”
Section: Resultsmentioning
confidence: 99%
“…It consists in an exfoliated monoisotopic h 11 BN crystal transferred onto a graphene/SiC(0001) substrate. It should be pointed out that charging effects in photoemission from a bulk-like flake of an insulating material can be avoided by thinning the material in the exfoliation process and by placing it on a conductive support (38). Indeed, our recent photoemission study showed that it is possible to resolve the π-band of exfoliated hBN on epitaxial graphene (39).…”
Section: Resultsmentioning
confidence: 99%
“…2(d) are obtained by integrating the intensity within the blue and magenta boxes on bare and WS 2 covered hBN shown in panel (c). The expected π * resonance is observed in addition to a shoulder which appears after SL WS 2 transfer [14]. Using secondary electron contrast from the t 2g resonance on the TiO 2 L-edge we are able to distinguish bare and WS 2 covered TiO 2 in Fig.…”
mentioning
confidence: 88%
“…This enables us to correlate the real-space (x, y)-dependent features of our sample with the "local" E(k)-dispersion. 34,36,37 This method leads to our observation of the SL WS (g) Summary of band maxima at Γ and K for SL WS 2 (red ticks) and MoS 2 /WS 2 (green ticks). The different VBM between the two regions has been highlighted with thin dashed lines.…”
Section: Resultsmentioning
confidence: 99%